Virtual Fitting and Hemodynamic Simulation of the EVAHEART 2 Left Ventricular Assist Device and Double-Cuff Tipless Inflow Cannula - Sonntag, Simon Johannes; Lipinski, Erin; Neidlin, Michael; Hugenroth, Kristin; Benkowski, Robert; Motomura, Tadashi; Kaufmann, Tim Arne Simon (ASAIO journal (1992), 2019)
Inflow malposition during surgery, postoperative pump migration, inflow obstruction, and right ventricular compression are major contributors to low flow and adverse events in patients with ventricular assist devices (VADs). These position abnormalities can lead to adverse events including ischemic stroke. To address these problems, we conducted a virtual anatomical fitting study and hemodynamic simulation on iterative cannula designs, resulting in the EVAHEART 2 with the novel double-cuff tipless (DCT) inflow cannula and smaller pump design. Anatomical fitting was based on computed tomography scans of six patients with heart failure, and a fluid-structure-integration (FSI) model of the left ventricle with a lumped parameter model of the entire cardiovascular system during VAD support was created. Using this model, the hemodynamics of three inflow cannula insertion lengths for two patient-specific ventricles were calculated for both full and partial VAD support. The DCT cannula with the smaller pump housing proved resistant to obstruction even when the pump housing was adjusted. The complete system also had a smaller pump pocket size than the other designs and avoided position abnormalities that commonly lead to adverse events. Compared with conventional cadaver studies, virtual fitting and numerical simulations are more beneficial and economical for iteratively designing medical devices.